Tau pathology associates with in vivo cortical thinning in Lewy body disorders. Issue 12 (27th October 2020) - Spotorno, Nicola; Coughlin, David G.; Olm, Christopher A.; Wolk, David; Vaishnavi, Sanjeev N.; Shaw, Leslie M.; Dahodwala, Nabila; Morley, James F.; Duda, John E.; Deik, Andres F.; Spindler, Meredith A.; Chen‐Plotkin, Alice; et al.
Abstract: Objectives: To investigate the impact of Alzheimer's disease (AD) co‐pathology on an in vivo structural measure of neurodegeneration in Lewy body disorders (LBD). Methods: We studied 72 LBD patients (Parkinson disease (PD) = 2, PD‐MCI = 25, PD with dementia = 10, dementia with Lewy bodies = 35) with either CSF analysis or neuropathological examination and structural MRI during life. The cohort was divided into those harboring significant AD co‐pathology, either at autopsy (intermediate/high AD neuropathologic change) or with CSF signature indicating AD co‐pathology (t‐tau/A β 1‐42  > 0.3) (LBD+AD, N  = 19), and those without AD co‐pathology (LBD−AD, N  = 53). We also included a reference group of 25 patients with CSF biomarker‐confirmed amnestic AD. We investigated differences in MRI cortical thickness estimates between groups, and in the 21 autopsied LBD patients (LBD−AD = 14, LBD+AD = 7), directly tested the association between antemortem MRI and post‐mortem burdens of tau, A β, and alpha‐synuclein using digital histopathology in five representative neocortical regions. Results: The LBD+AD group was characterized by cortical thinning in anterior/medial and lateral temporal regions ( P  < 0.05 FWE‐corrected) relative to LBD−AD. In LBD+AD, cortical thinning was most pronounced in temporal neocortex, whereas the AD reference group showed atrophy that equally encompassed temporal, parietal and frontal neocortex. In autopsied LBD, we found an inverse correlation with cortical thickness and post‐mortem tau pathology, while cortical thickness was not significantly associated with A β or alpha‐synuclein pathology. Interpretation: LBD+AD is characterized by temporal neocortical thinning on MRI, and cortical thinning directly correlated with post‐mortem histopathologic burden of tau, suggesting that tau pathology influences the pattern of neurodegeneration in LBD.